2020
DOI: 10.1002/gch2.202000038
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 on Psychology among the University Students

Abstract: threatens to cause a humanitarian crisis in this country. According to the World Bank data, in Bangladesh, 15% of workers earn more than 500 taka ($5.90) a day and the economic shutdown sparked by COVID-19 endangers millions of livelihoods imminently. The people could meet their daily expenditures, sent their children to school, and expected that they could save money for an emergency health crisis. The majority of villagers depend on remittances from the cities or overseas. However, for the current global cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
116
3
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(135 citation statements)
references
References 22 publications
11
116
3
5
Order By: Relevance
“…), financial uncertainty, exposure to COVID-19 news in social media and mass media Mild to extremely severe Faisal et al (2021) 33 University students; 874 Snowball Age group: 17 to 38 years; Mean age: 22.83± 2.79 y GAD-7 and CESD-R-10 A ≥10, D ≥10 A: 40% D:72% A and D: Worrying about the effects of COVID-19 A: Moderate to severe D: NR Islam et al (2020) 34 University students; 3122 Convenience Age group: 18 to 29 years; Mean age: 21.4 ± 2 y DASS-21 A ≥ 8, D ≥10, S ≥15 A: 71.5% D:76.1% S: 70.1% D, A, and S: Gender, age, having ≥5 family members, residence, physical exercise, sleep dissatisfaction, more internet time, academic dissatisfaction due to the COVID-19 circumstances, and smoking status At least mild symptoms Dhar et al (2020). 35 University students; 15,543 NR NR GAD-7 NR A: 96.82% Gender, residence, living with their parents, financial condition, being infected with COVID‐19 among relatives or friends Mild to severe Abbreviations : A, anxiety; D, depression; S, stress; NR, not reported; PHQ, Patient Health Questionnaire; GAD, Generalized Anxiety Disorder; HADS, Hospital Anxiety and Depression Scale; DASS-21, Depression, Anxiety, Stress Scale 21; CESD-R-10, Center for Epidemiologic Studies Depression Scale Revised. …”
Section: Resultsmentioning
confidence: 99%
“…), financial uncertainty, exposure to COVID-19 news in social media and mass media Mild to extremely severe Faisal et al (2021) 33 University students; 874 Snowball Age group: 17 to 38 years; Mean age: 22.83± 2.79 y GAD-7 and CESD-R-10 A ≥10, D ≥10 A: 40% D:72% A and D: Worrying about the effects of COVID-19 A: Moderate to severe D: NR Islam et al (2020) 34 University students; 3122 Convenience Age group: 18 to 29 years; Mean age: 21.4 ± 2 y DASS-21 A ≥ 8, D ≥10, S ≥15 A: 71.5% D:76.1% S: 70.1% D, A, and S: Gender, age, having ≥5 family members, residence, physical exercise, sleep dissatisfaction, more internet time, academic dissatisfaction due to the COVID-19 circumstances, and smoking status At least mild symptoms Dhar et al (2020). 35 University students; 15,543 NR NR GAD-7 NR A: 96.82% Gender, residence, living with their parents, financial condition, being infected with COVID‐19 among relatives or friends Mild to severe Abbreviations : A, anxiety; D, depression; S, stress; NR, not reported; PHQ, Patient Health Questionnaire; GAD, Generalized Anxiety Disorder; HADS, Hospital Anxiety and Depression Scale; DASS-21, Depression, Anxiety, Stress Scale 21; CESD-R-10, Center for Epidemiologic Studies Depression Scale Revised. …”
Section: Resultsmentioning
confidence: 99%
“…A survey of 1,770 Chinese citizens showed a 47.1% prevalence of depression and an 18.2% prevalence of major depressive symptoms due to social isolation and other reasons ( Ran et al, 2020 ). Similarly, a longitudinal investigation showed that the stress of the pandemic has had a significant impact on the college students ( Wang et al, 2020 ), who showed varying degrees of anxiety and depression due to factors such as financial pressure and academic delays ( Dhar et al, 2020 ). Therefore, it is important to focus on the emotional impact of the pandemic on people.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, both genders should be involved in future studies to investigate any potential differences between their educational experiences and validate the anticipated equality in educational attainments. The second limitation is that the study should be reproduced in appropriate circumstances without potential physiological effects such as the predominance of stress and anxiety among home-quarantined students who are affected by the pandemic COVID-19 confinement, to validate the impact of the hybrid online-flipped teaching approach on the attainment of CLOs (Dhar et al 2020 ; Maqsood et al 2021 ; Chaturvedi et al 2021 ; Tang et al 2020 ).…”
Section: Methodsologymentioning
confidence: 99%
“…The impact of the COVID-19 epidemic on teaching labs' educational outcomes is not clear yet. Although numerous publications exist in the literature examined the epidemic impact on psychological behavior among undergraduates (Dhar et al 2020 ; Maqsood et al 2021 ; Chaturvedi et al 2021 ; Tang et al 2020 ) and on medical education (Hung et al 2020 ; Liu et al 2020 ; Loch et al 2021 ; Shih et al 2020 ), no empirical study currently exists that evaluated the impact of the COVID‐19 on online Lab education, especially in engineering curricula. In this paper, we study how have hybrid online-flipped learning pedagogy of teaching laboratory courses impacted course learning outcomes in the Unit Operations Laboratory course in the chemical engineering program at Qatar University to alleviate the pandemic's impact COVID-19 confinement.…”
Section: Introductionmentioning
confidence: 99%